Coverage versus Frequency: Exploring Service Variability among Informal Public Transport Operators in South Africa - Manaseh Angurini; Christo Venter (Findings)
Informal public transport operators often make routing and dispatch decisions on the fly, as demand and traffic conditions change. This may cause highly variable and unpredictable services for passengers. This paper examines variability in spatial coverage, route alignment, and service frequency over time and space using GPS data in a medium-sized city. We propose using a GINI coefficient to measure the spatial concentration of services. While considerable variation exists, consistent high-frequency routes exist where many services are concentrated throughout the day. In lower demand areas service availability and routes vary much more, causing significant variations in service provision by direction.